2020
DOI: 10.3390/w12061693
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics Applied to Terraced Agroecosystems: The Case Study of Assaragh (Anti-Atlas Mountains, Morocco)

Abstract: Terraced agroecosystems (TAS)—apart from being an important cultural heritage element—are considered vital for sustainable water resource management and climate change adaptation measures. However, this traditional form of agriculture, with direct implications in food security at a local scale, has been suffering from abandonment or degradation worldwide. In light of this, the need to fully comprehend the complex linkage of their abandonment with different driving forces is essential. The identification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 75 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…However, it is now that the negative consequences for the soil and the landscape are starting to appear and are becoming spectacular. Other authors have shown it in the Anti-Atlas as well [17]. The abandonment of terraces, mainly due to social driving forces (little exchange between generations and emigration) rather than natural or ecological (droughts or a lack of water resources), is leading to land degradation and the loss of an important cultural heritage.…”
Section: The Abandonment Of the Terraces In The Territory Of The Villmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now that the negative consequences for the soil and the landscape are starting to appear and are becoming spectacular. Other authors have shown it in the Anti-Atlas as well [17]. The abandonment of terraces, mainly due to social driving forces (little exchange between generations and emigration) rather than natural or ecological (droughts or a lack of water resources), is leading to land degradation and the loss of an important cultural heritage.…”
Section: The Abandonment Of the Terraces In The Territory Of The Villmentioning
confidence: 99%
“…The loss of agricultural potential at the level of the terraces strongly compromises rural development and compromises the sustainability of the cultural heritage that these landscapes constitute in the Anti-Atlas [17]. Indeed, the degradation of natural resources (water, soil and vegetation) is a factor in the discouragement of the population, which favors the rural exodus and, at the same time, the abandonment of the terraces.…”
mentioning
confidence: 99%
“…The paper by Sabir [20] closes the Special Issue, showing how the effects of land abandonment in the terraces of Anti-Atlas (described by Boselli in [17]) lead to a reduction of infiltration in unmanaged terraced landscapes, even after few years. The author suggested immediate action to rehabilitate and restore the socio-ecological systems of terraced areas, to avoid consequent hydrological and hydrogeological hazards.…”
Section: Overview Of the Special Issuesmentioning
confidence: 94%
“…The Special Issue also hosted multi-disciplinary research efforts, such as the work by Boselli et al [17], who studied the dynamics of land abandonment in the terraced landscapes of Anti-Atlas (Morocco) with a system dynamics approach. The analysis highlighted how the abandonment of the terraced agroecosystems in the area is mainly driven by social issues rather than by climatic changes.…”
Section: Overview Of the Special Issuesmentioning
confidence: 99%
See 1 more Smart Citation